Development of STEM-EDP-Based Student Worksheets to Improve Students' Critical Thinking Skills at SMP Negeri 17 Samarinda - Cyndirela; Lambang Subagiyo; Sonja Verra Tinneke Lumowa; Makrina Tindangen; Yusak Hudiyono; Akhmad; Vandalita M.M. Rambitan; Masitah (Jurnal Penelitian Pendidikan IPA, 2025)
Critical thinking skills are important for students, but not all students possess strong critical thinking abilities. This study aims to develop a STEM-EDP-based Student Worksheet media to improve students' critical thinking skills in the topics of Ecology and Biodiversity. This research uses the ADDIE development model, developed by Robert Reiser and Michael Molenda, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. The developed media was validated by experts in content and media, with the media expert validation result being 91% and the content expert validation result being 94%, both categorized as highly valid. Practicality testing was obtained from practicality questionnaires filled out by both teachers and students. The student practicality questionnaire resulted in 90.5%, categorized as very practical, and the teacher practicality test resulted in 90%, also categorized as very practical. The effectiveness of critical thinking skills was assessed through pretest and posttest results, using the N-Gain test, which resulted in a score of 0.7, categorized as high. Therefore, it can be concluded that the use of STEM-EDP-based Student Worksheets to improve students' critical thinking skills is effective and categorized as high.